An Analysis of Students’ Reading Comprehension Difficulties of Eighth Grade Students at SMP Negeri 4 Tegalalang - Saraswati, N.K.R.; Dambayana, P.E.; Pratiwi, N.P.A (Jurnal IKA, 2021)
This study aimed to investigate students’ reading comprehension difficulties of eighth grade students at SMP N 4 Tegallalang. This study used descriptive quantitative method. To run this research, 129 eighth grade students of SMP N 4 Tegallalang in the academic year 2020/2021 were chosen as the sample. The data of students’ reading comprehension difficulties collected through reading comprehension test. The result of students’ reading comprehension test indicated eight grade students of SMP N 4 Tegallalang have difficulty in all five aspects of reading comprehension. Those were determining main idea, locating reference, understanding vocabulary meaning, making inference, and finding specific information. Determining main idea was the most difficult aspect faced by students which got 72% of the percentage of difficulty. It was followed by locating reference which got 70%. For students’ difficulty in understanding vocabulary and finding specific information the percentage of difficulty were 68% and 67% which only one percent difference. Meanwhile, students’ difficulty in making inference got the lowest of the percentage difficulty which was 63%.Keywords: Difficulties; Reading; Reading Comprehension.